Analisis Pengaruh Intensitas Turnover Karyawan pada PT XYZ Brebes - Disiya Intan Setiyawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
Machines, Materials and Manpower are the three main elements in production, if one of them is lacking it will affect productivity at work, so that the production output results will also be affected by the lack of these three elements. The workforce in a company must be considered in terms of welfare at work so that there is no spike in employee turnover rates. Turnover is the process of leaving a company's workforce due to several factors. Employee turnover greatly affects productivity at work, if the workforce in a company is lacking, then the production output figure will also decrease, this greatly affects the company's income later and will reduce consumer confidence. In this study, it focuses on the intensity of employee turnover at PT. XYZ located in Brebes, there are several factors causing employee turnover, including low income, the presence of many factories close to where employees live. The method used in this study is descriptive qualitative. Data collection techniques in the form of direct interviews with employees at PT. XYZ.